2017
DOI: 10.1021/acs.jpcc.7b00913
|View full text |Cite
|
Sign up to set email alerts
|

Role of Local Carbon Structure Surrounding FeN4Sites in Boosting the Catalytic Activity for Oxygen Reduction

Abstract: Development of effective nonprecious metal and nitrogen codoped carbon catalysts for the oxygen reduction reaction (ORR) requires a fundamental understanding of the mechanisms underlying their catalytic activity. In this study, we employed the first-principles density functional theory calculations to predict some key parameters (such as activation energy for O−O bond breaking and free-energy evolution as a function of electrode potential) of ORR on three FeN 4 -type active sites with different local carbon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 47 publications
4
135
2
3
Order By: Relevance
“…In Table S7 and Figure S15a in the Supporting Information, we compare the off‐plane distortion (Δ h ) of carbon layers and the oxygen adsorption energy of the modelled FeN 4 sites. At first, we used the value of the limiting potential defined as the maximum applied electrode potential to make ORR thermodynamically favorable, as a parameter gauging the ORR activity of the differently strained FeN 4 sites …”
Section: Resultsmentioning
confidence: 99%
“…In Table S7 and Figure S15a in the Supporting Information, we compare the off‐plane distortion (Δ h ) of carbon layers and the oxygen adsorption energy of the modelled FeN 4 sites. At first, we used the value of the limiting potential defined as the maximum applied electrode potential to make ORR thermodynamically favorable, as a parameter gauging the ORR activity of the differently strained FeN 4 sites …”
Section: Resultsmentioning
confidence: 99%
“…Based on the dissociative mechanism, the edge-hosted MN 2+2 sites (M = Fe, Co) were predicted to have higher ORR activity than in-plane MN 4 due to the lower dissociation barrier of OOH* on the MN 2+2 site. [63,97] Therefore, MOFs precursors with smaller particle sizes tend to produce more MN 2+2 sites after thermal activation, due to the higher ratio of edge area relative to the basal plane area. Our recent work showed that the particle sizes of Fe and Co SACs are tunable via controlling the size of the MOFs precursors during the synthesis in solution.…”
Section: Effect Of the Ratio Of Metal Precursorsmentioning
confidence: 99%
“…DFT caculations reveal that edge and pore defects play a key role in modulating the electronic structure of adjacent FeN 4 sites, leading to an optimized adsorption energy of the intermedates and a remarkably decreased ORR barrier compared to the nondefective configuration. [97] Synergism of Dual Metal Sites: The construction of dual metal sites has been demonstrated to be highly effective for enhanced ORR performance. A series of N-coordinated dual metal sites, including Co-Fe, [67][68][69][70] Co-Pt, [53] Zn-Co, [71,72] and Fe-Mn [73] sites, have been developed.…”
Section: The Oxygen Reduction Reactionmentioning
confidence: 99%
“…In a detailed work, He et al [158] present experimental support for the presence of a slightly different active site, which they refer to as Co-N 2+2 in line with earlier theoretical studies. [159] By using a surfactant (Pluronic F127 block copolymer) assisted approach in combination with zeolitic imidazolate framework they achieved highly dispersed single Co-atomic sites. Different from most other studies, they showed support from EXAFS data for an average coordination number 3.6.…”
Section: Cobalt-nitrogen-based Catalystsmentioning
confidence: 99%
“…Whether this unambiguously support the presence of Co-N 2+2 sites, seen as Co-N 4 moieties bridging over two adjacent armchair graphitic edges (Figure 6), is not fully clear. Nonetheless, it is interesting to note that Liu et al [159] proposed that these type of sites can only form for highly porous supports such as that used by He et al It is also interesting that the catalyst by He et al so far exhibits the best ORR performance in acidic conditions among the platinum group metal-free and Fe-free catalysts ( Table 2). Different from other reports in this section, who all report active sites comprising a single metal atom coordinated to nitrogen, Xiao et al [76] reported high activity for a catalyst containing at least in part an active site comprising Co 2 -N 5 , that is, two Co atoms coordinated to nitrogen atoms.…”
Section: Cobalt-nitrogen-based Catalystsmentioning
confidence: 99%